2008
DOI: 10.1074/jbc.m703772200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biophysical Analysis of the DNA Binding Properties of Myelin Transcription Factor 1

Abstract: Zinc binding domains, or zinc fingers (ZnFs), form one of the most numerous and most diverse superclasses of protein structural motifs in eukaryotes. Although our understanding of the functions of several classes of these domains is relatively well developed, we know much less about the molecular mechanisms of action of many others. Myelin transcription factor 1 (MyT1) type ZnFs are found in organisms as diverse as nematodes and mammals and are found in a range of sequence contexts. MyT1, one of the early tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
53
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 50 publications
8
53
1
Order By: Relevance
“…3, A and B) reveals the sequence AAAGTTCA (palindromic sequence is underlined) as the F4F5 interaction surface. These data are in good agreement with our SPR and NMR analysis of the F5-DNA interaction (14), which showed that F5 has a footprint on the DNA that comprises the smaller AGT motif.…”
Section: Identification Of the Dna-binding Interface Of The Myt1 Doubsupporting
confidence: 81%
See 4 more Smart Citations
“…3, A and B) reveals the sequence AAAGTTCA (palindromic sequence is underlined) as the F4F5 interaction surface. These data are in good agreement with our SPR and NMR analysis of the F5-DNA interaction (14), which showed that F5 has a footprint on the DNA that comprises the smaller AGT motif.…”
Section: Identification Of the Dna-binding Interface Of The Myt1 Doubsupporting
confidence: 81%
“…We recently assessed the binding of MyT1 to DNA and showed that the fifth zinc finger can fit into the DNA major groove and make contacts with the central AGT of the consensus sequence (14). Our data also indicated that double-finger constructs of both the two-ZF and the four-ZF clusters (F1F2, F4F5, F5F6, and F6F7) interact with the full AAAGTT consensus site with a higher affinity than does a single finger.…”
supporting
confidence: 48%
See 3 more Smart Citations